Phyto chemical and memory enhancer activity of the 2 polyherbal formulation: comparative activity on AlCl3 induced albino wistar rats - Patel, Hardik; Patel, Janmejay; Patel, Payal; Patel, Apurva; Patel, Kunj; Saiyad, M.S.Hasmi (International Journal of Pharmacology and Toxicology, 2016)
Background: Epidemiological studies of Indian population reveal that dementia is largely a hidden problem in India. Ayurveda claims several plants are beneficial in cognitive disorders. Pharmaco-epidemiological studies reveal that herbal and allopathic learning and memory enhancing medicines are becoming very popular among Indian population.Methodology: The present study was aimed at investing the effects of Dr. Brain Syrup and Capsule, Ayurvedic polyherbal formulation on memory enhancing activity in albino wistar rats. Drugs were administered through intraperitoneal at therapeutic dose for 28 days to different groups of the rats. Elevated Plus maze (EPM) and Radial Arm maze apparatus were served as the evaluating tool to identify the Transfer Latency (TL) in EPM and Average time taken to reach right arm in Radial Arm Maze models. Cognitive impairment was induced by administering the AlCl3 at dose of 4.2mg/kg i.p.Result: At the end of 4 weeks, Transfer Latency in model control group increased to 90±0.00 sec as compared to47.66±7.39 sec (p<0.01) in Normal control rats. Dr. Brain Syrup and Capsule were significantly attenuated TL to 19.5±4.27 and 21.16±2.83 sec respectively as compared to Model Control Group after 4 weeks. Moreover, Treatment with Dr. Brain Syrup and Capsule reduced the mean time to find the right arm to 20.83±2.08 and 27.16±1.17 sec (p<0.01) as compared to 129.66±4.60 sec in Model control group after 4 weeks.Conclusion: Dr. Brain Syrup and Capsule showed significant activity in improvement in Memory by evaluating the TL and Average time period in 2 different instruments in 4 weeks of the drug treatment.